2022
DOI: 10.3390/fermentation8020039
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of 2-Phenylethanol Production from Sweet Whey Fermentation Using Kluyveromyces marxianus

Abstract: The growing demand for natural products benefits the development of bioprocesses to obtain value-added compounds using residues such as sweet whey, which is rich in lactose. The yeast Kluyveromyces marxianus can ferment sweet whey to obtain 2-phenylethanol (2-PhEtOH), which is a superior alcohol with a rose aroma. Such fermentation only requires the addition of L-phenylalanine (precursor) and (NH4)2SO4 (salt). Therefore, it was sought to improve the fermentation conditions to produce 2-PhEtOH, which, in turn, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
0
10
1
Order By: Relevance
“…However, the inorganic nitrogen in M6 was not consumed during the experiment, suggesting that the cell growth was supported by the nitrogen supplied by L‐Phe. It is reported that activation of the Ehrlich pathway, in yeasts, is favored when L‐Phe is used as sole nitrogen source, since in the presence of more easily digestible nitrogen sources, such as ammonium salts, the expression of enzymes involved in that pathway are low or even negligible 12,44 . In order to confirm if this also applies to the bacterium A. soli ANG344B, an experiment with L‐Phe as sole nitrogen source was performed (M7) (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…However, the inorganic nitrogen in M6 was not consumed during the experiment, suggesting that the cell growth was supported by the nitrogen supplied by L‐Phe. It is reported that activation of the Ehrlich pathway, in yeasts, is favored when L‐Phe is used as sole nitrogen source, since in the presence of more easily digestible nitrogen sources, such as ammonium salts, the expression of enzymes involved in that pathway are low or even negligible 12,44 . In order to confirm if this also applies to the bacterium A. soli ANG344B, an experiment with L‐Phe as sole nitrogen source was performed (M7) (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…marxianus CCA510 to produce 2‐phenyl‐ethanol (2‐FE), a higher aromatic alcohol widely used in the perfume industry, [ 54 ] that was detected in the experiment using CABH (data not shown). The genus Kluyveromyces has been widely cited as a potential producer of 2‐FE [ 55–57 ] and reports indicate that its production by yeasts can occur both in the presence and absence of phenylalanine, the natural precursor of this alcohol, and the aeration rate is an important factor for its synthesis. [ 58 ] In this way, it is possible to verify that the CABH is a promising medium for the production of xylitol and that it can also be used as a fermentation medium to obtain other bioproducts of industrial importance.…”
Section: Resultsmentioning
confidence: 99%
“…The consumption of L-Phe is regulated by its initial concentration and its transamination to obtain energy during the exponential growth phase [ 34 , 35 ]. L-Phe transamination depends on the presence of α-ketoglutarate, which is the electron acceptor of the reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analysis showed that 2PE production was facilitated when BSY was used as a supplement of whey in comparison to the use of yeast extract and peptone ( Supplementary Material Table S2 ). Alonso-Vargas et al (2022) [ 34 ] studied the fermentation of whey enriched with 4.5 g/L of L-Phe and 1 g/L of (NH 4 ) 2 SO 4 using K. marxianus . They observed a 2PE concentration of 1.17 g/L at 72 h, leading to a productivity of 0.02 g 2PE /L·h.…”
Section: Discussionmentioning
confidence: 99%